Study of Iranian Islamic Philosophy at Rausyan Fikr Institute and Religious Reason - ulya, ulya; Abdullah, Abdullah (ADDIN, 2025)
Rausyan Fikr Institute in Yogyakarta is often claimed as one of the Shia agents in the midst of Indonesian society that adheres to the Sunni tradition. This study analyzes the religious discourse developed there and the contribution of the discourse to the reasoning and model of religiosity while employing qualitative-descriptive research. The data source was from the director, a tutor at Rausyan Fikr Institute. The other data source is the participants of the study. Data collection was conducted through semi-structured interviews, non-participatory observation, and documentation. The data analysis applied the steps of data reduction, data display, and data verification or conclusions. The results found that the religious discourse developed at Rausyan Fikr is Iranian Islamic Philosophy, especially the thoughts of Murtadha Muthahhari. Iran is often identified with Shia. Therefore, the existence of Rausyan Fikr has been questioned. Apart from these problems, the study of Iranian Islamic Philosophy discussed at Rausyan Fikr contributed positively to the shaping of the reasoning and model of religiosity of its participants, which is those who have a religion should not be instant and dogmatic, but must be based on a critical and rational attitude. In addition, having a religion should not be exclusive and extremist, but must be inclusive and moderate. This finding enriches insights about the dynamics of Islamic discourse, especially the study of Islamic philosophy in Indonesia, and also enriches the literature on minority community studies.